Building Digital Communities as a Tool for Social Engineering in the New Capital City (Ibu Kota Nusantara): Penelitian - Fikri Reza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The relocation of Indonesia's capital city to Ibu Kota Nusantara (IKN) in East Kalimantan marks a transformative urban development project aimed at addressing long-standing national challenges, including urban congestion, economic disparity, and environmental degradation. This paper explores the potential of digital communities as tools for social engineering in the context of this massive project. It reviews how digital platforms can be leveraged to foster civic participation, promote transparency, and facilitate collaboration between residents and the government, thus ensuring inclusivity and resilience in the newly built city. The research identifies key challenges, such as the digital divide and data privacy concerns, while highlighting opportunities for social innovation and the inclusion of marginalized groups. Ultimately, digital communities offer significant potential to make IKN a model for smart, sustainable, and inclusive urban development.